Consumer Behaviour and Role of Consumer Research in Marketing - Kumar, Rakesh (Journal of Commerce and Trade, 2017)
The study of consumer behaviour is the study of how individual make decisions to spend their available resources (money, time, and effort) on consumption-related items. It includes the study of what they buy, why they buy it, how they buy it, when they buy it, where they buy it, and how often they buy it. Consumer behaviour is the process whereby, individuals decide whether, what, when, where, how, and from whom to purchase goods and services. The role of consumer research in marketing has been increased significantly. In this research paper an attempt has been made to provide an understanding to the concept Consumer behaviourand to highlight the role of consumer research in marketing.